3D Gravity Modeling of Complex Salt Features in the Southern Gulf of Mexico - Mauricio Nava-Flores; Carlos Ortiz-Aleman; Mauricio G. Orozco-del-Castillo; Jaime Urrutia-Fucugauchi; Alejandro Rodriguez-Castellanos; Carlos Couder-Castañeda; Alfredo Trujillo-Alcantara (International Journal of Geophysics)
We present a three-dimensional (3D) gravity modeling and inversion approach and its application to complex geological settings characterized by several allochthonous salt bodies embedded in terrigenous sediments. Synthetic gravity data were computed for 3D forward modeling of salt bodies interpreted from Prestack Depth Migration (PSDM) seismic images. Density contrasts for the salt bodies surrounded by sedimentary units are derived from density-compaction curves for the northern Gulf of Mexico’s oil exploration surveys. By integrating results from different shape- and depth-source estimation algorithms, we built an initial model for the gravity anomaly inversion. We then applied a numerically optimized 3D simulated annealing gravity inversion method. The inverted 3D density model successfully retrieves the synthetic salt body ensemble. Results highlight the significance of integrating high-resolution potential field data for salt and subsalt imaging in oil exploration.